Influence of IAA, IBA and GA on growth and 3 yield of onion (Allium cepa L.) (Indian Journal of Arid Horticulture, 2013)
Onion (Allium cepa L.) is among the most before transplanting. Rest of the N was given as a single  important vegetable / medicinal crop grown in India. This dose 25 days after transplanting. All other recommended  crop introduced in India from Central Asia, the primary cultural practices were adopted to raise a good crop. Each  centre of origin. Onion must have been grown in India from plot consisted of five rows of 3 m length with 15 cm spacing  very ancient times as their utility as medicinal herbs has between rows and 10 cm between plants. Furrow method of  been mentioned in the medicinal treaties like “Charka irrigation was followed.
Keywords: Durgapura; influencing